Adiposity and Outcome After Ischemic Stroke: Obesity Paradox for Mortality and Obesity Parabola for Favorable Functional Outcomes. Issue 1 (January 2021) - Liu, Zuolu; Sanossian, Nerses; Starkman, Sidney; Avila-Rinek, Gilda; Eckstein, Marc; Sharma, Latisha K.; Liebeskind, David; Conwit, Robin; Hamilton, Scott; Saver, Jeffrey L.
Abstract : Background and Purpose: A survival advantage among individuals with higher body mass index (BMI) has been observed for diverse acute illnesses, including stroke, and termed the obesity paradox. However, prior ischemic stroke studies have generally tested only for linear rather than nonlinear relations between body mass and outcome, and few studies have investigated poststroke functional outcomes in addition to mortality. Methods: We analyzed consecutive patients with acute ischemic stroke enrolled in a 60-center acute treatment trial, the NIH FAST-MAG acute stroke trial. Outcomes at 3 months analyzed were (1) death; (2) disability or death (modified Rankin Scale score, 2–6); and (3) low stroke-related quality of life (Stroke Impact Scale<median). Relations with BMI were analyzed univariately and in multivariate models adjusting for 14 additional prognostic variables. Results: Among 1033 patients with acute ischemic stroke, average age was 71 years (±13), 45.1% female, National Institutes of Health Stroke Scale 10.6 (±8.3), and BMI 27.5 (±5.6). In both unadjusted and adjusted analysis, increasing BMI was linearly associated with improved 3-month survival ( P =0.01) odds ratios in adjusted analysis for mortality declined across the BMI categories of underweight (odds ratio, 1.7 [CI, 0.6–4.9]), normal (odds ratio, 1), overweight (0.9 [CI, 0.5–1.4]), obese (0.5, [CI, 0.3–1.0]), and severely obese (0.4 [CI, 0.2–0.9]). In unadjusted analysis, increasing BMI showed a U-shaped relation to poststroke disability or death (modified Rankin Scale score, 2–6), with odds ratios of modified Rankin Scale score, 2 to 6 for underweight, overweight, and obese declined initially when compared with normal weight patients, but then increased again in severely obese patients, suggesting a U-shaped or J-shaped relation. After adjustment, including for baseline National Institutes of Health Stroke Scale, modified Rankin Scale score 2 to 6 was no longer related to adiposity. Conclusions: Mortality and functional outcomes after acute ischemic stroke have disparate relations with patients' adiposity. Higher BMI is linearly associated with increased survival; and BMI has a U-shaped or J-shaped relation to disability and stroke-related quality of life. Potential mechanisms including nutritional reserve aiding survival during recovery and greater frequency of atherosclerotic than thromboembolic infarcts in individuals with higher BMI. Abstract : Supplemental Digital Content is available in the text.